Kepemimpinan Visioner dalam Manajemen Pendidikan Transformatif: Strategi Peningkatan Mutu dan Relevansi di Perguruan Tinggi Keagamaan Islam Negeri - Adisel Adisel; Robeet Thadi; Moch.Iqbal; Sukarno Sukarno (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the implementation of visionary leadership in transformative educational management and identify strategies for improving the quality and relevance of education at State Islamic Religious Universities (PTKIN), with a focus on UIN Raden Fatah Palembang. The research method used was a qualitative case study approach. Data were collected through semi-structured interviews, participant observation, and document analysis, followed by thematic analysis. The results indicate that visionary leadership plays a key role in educational transformation through the implementation of strategic policies that include digitalization of academic services, human resource development, curriculum internationalization, strengthening of quality assurance systems, and multi-stakeholder collaboration. These strategies have resulted in improved educational quality, as evidenced by the increased quality of scientific publications, research culture, study program accreditation, and the effectiveness of academic services. Furthermore, educational relevance has been enhanced through the development of an Outcome-Based Education (OBE) curriculum, the integration of Islamic values ​​with global competencies, student entrepreneurship programs, and strengthening partnerships with the business world, industry, and international institutions. The conclusion of this study indicates that visionary leadership is a key factor in realizing transformative educational management that can sustainably improve the quality and relevance of PTKIN education, making it more adaptive to global challenges without neglecting Islamic identity and values.   Keywords: Educational Digitalization, Visionary Leadership, Transformative Educational Management, Educational Quality